LANCAR Rancang Bangun Alat Sebagai Layanan Notifikasi Air conditioner Yang Rusak Pada Bagian Kompresor - Darmawan, I Gede Agus; Jasa, Lie; Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i02.P13, 2020)
Indonesia is a tropical country that has two seasons, namely the rainy season and the dry season. During the dry season, the weather gets hot so AC technology (Air Conditioner) technology is really needed by the people of Indonesia. Every day, air conditioners are often used to cool the air, so the use of air conditioners is very routine in the dry season. Ac needs to be maintained regularly so that the AC is not easily damaged. Ac is divided into two parts, namely indoor and outdoor. Indoor and outdoor are connected through copper pipes which are freon gas lines. Freon gas will be pumped through the outdoor using a compressor engine to suppress the flow of freon gas so it flows into the evaporator section of the indoor and the compressor will suck the freon gas again to the condenser section on the outdoor because the compressor is the most important part in the air conditioner, the compressor must be routinely maintained by knowing the amperage performance on the compressor. So the purpose of this research is to monitor the performance of the compressor. This monitoring is done by installing a LANCAR (broken air conditioner notification service). LANCAR has three parts, namely electronics as a tool to detect compressor performance amperes, applications as notification media as well as for monitoring compressor amperes and database as compressor amperage data storage. Electronics used such as NodeMCU esp 8266, current sensor, vibration sensor and 1 channel relay module. These parts will be connected to the IoT (internet of things) system where the device is able to provide notifications when the compressor is damaged and the amperage data on the compressor will be stored in a database so that it can later be seen by the AC owner.